Perbandingan Aktivasi Otot Trisep pada Kondisi Kontraksi dan Relaksasi Menggunakan Elektromiografi (EMG) Portabel Berbasis Android - Hani Nur Endah; Heni Sumarti; Hamdan Hadi Kusuma (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
EMG is a method widely used to estimate muscle activity and can help understand how muscles interact with each other that affects human movement control. In this study to detect muscle interaction during contraction and relaxation of the triceps elbow muscle. Non-invasive techniques are used in this study to characterize muscle electrical activity. In this study, additional loads were added to the contraction movement to observe whether there was a relationship between changes in muscle activity and the load carried by the muscle in male and female subjects. Signal changes can be read by the microcontroller ADC and then sent to Blynk. This study shows that during the relaxation movement, the subject has an average Vpp value of 0.007 V. When performing the contraction movement, the average Vpp value increases to 0.024 V. When a 2 kg load is added, the average Vpp value increases to 0.027 V. The heavier the load carried, the Vpp value of muscle activity also increases.